Optimization Study of Sequencing Batch Reactor (SBR) Poultry Wastewater Operation in Low Influent Flow Rate - Mohamad Shukri, Muhammad Amir Redzuan; Nor Haslina Hashim (Progress in Engineering Application and Technology, 2024)
This study examines the effectiveness of Sequencing Batch Reactor (SBR) technology in treating poultry slaughterhouse wastewater. The study monitored the parameters of pH, SV30, DO, AN, MLSS, COD, and BOD to evaluate the efficiency of the biological treatment process. The results suggest that SBR technology can be effective in removing organic matter and nitrogen from poultry wastewater. The comprehensive results reveal the effectiveness of SBR in removing suspended solids, microorganisms, nitrogen, and organic matter from the wastewater. The study underscores the importance of monitoring these parameters for assessing treatment efficacy and highlights the potential of SBR as a promising solution for sustainable poultry wastewater treatment. However, the study also highlights the importance of continuous monitoring and optimization of treatment processes to ensure their effectiveness.